2014
DOI: 10.1002/ejoc.201402045
|View full text |Cite
|
Sign up to set email alerts
|

Transition‐Metal‐Free Approach to 4‐Ethynylpyrimidines via Alkenynones

Abstract: A practical approach to the synthesis of 4‐ethynylpyrimidines by the condensation of arylamidines with 2‐aryl‐1‐ethoxy‐5‐(trimethylsilyl)pent‐1‐en‐4‐yn‐3‐ones has been developed. As these latter ketones are easily accessible from bis(trimethylsilyl)acetylene and arylacetyl chlorides, the regioselective condensation reported herein provides a facile access to both TMS‐protected and unprotected 4‐ethynylpyrimidines in yields of up to 85 %.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…Moreover, regioselective processing of corresponding reactions is provided by imbalance of three electrophilic centers of cross-conjugated enynones . Combining the factors of high activity and selectivity allows development of effective methods for synthesis of a variety of heterocycles, such as for pyrrolone, 4-oxodihydrothiopyran, indole, pyrazole, pyrimidine, and other compounds with more complex structures . Just recently, the expansion of pent-1-en-4-yn-3-ones was balanced with operation of current methods of metal complex catalysis , as well as with application of superelectrophilic activation .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, regioselective processing of corresponding reactions is provided by imbalance of three electrophilic centers of cross-conjugated enynones . Combining the factors of high activity and selectivity allows development of effective methods for synthesis of a variety of heterocycles, such as for pyrrolone, 4-oxodihydrothiopyran, indole, pyrazole, pyrimidine, and other compounds with more complex structures . Just recently, the expansion of pent-1-en-4-yn-3-ones was balanced with operation of current methods of metal complex catalysis , as well as with application of superelectrophilic activation .…”
Section: Introductionmentioning
confidence: 99%
“…We selected enynone 1a and 3(5)-(4-methylphenyl)-1 H -pyrazol-5­(3)-amine ( 2c ) as model substrates for optimization of the reaction conditions. Previously, we showed that ethanol is the solvent of choice for reactions of enynones 1 with hydrazines and amidines, and therefore, the first experiment was carried out in ethanol at 80 °C in a sealed vessel. To our delight, no further optimization was needed because the single product was isolated in 85% yield (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…UV–vis spectra were recorded for 10 –5 M solutions in CHCl 3 , and extinction coefficients are given in parentheses. Preparation of enynones 1a – e was described previously …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have designed a straightforward method for the synthesis of 2-(trimethylsilylmethylene)­pyrrol-3-ones bearing various substituents at 1- and 4-positions of the pyrrole core. The key starting compounds are cross-conjugated TMS-protected enynones 1 , readily available from bis­(trimethylsilyl)­acetylene and arylacetyl chlorides . Previously we thoroughly investigated the reactions of compounds 1 with binucleophiles, and herein we report the results obtained by employment of amines in reactions with enynones 1 .…”
Section: Introductionmentioning
confidence: 99%